Evaluasi Pembelajaran Akuntansi Dasar Usaha Dagang pada Siswa SMA ABC di Surabaya - Budianto Tedjasuksmana; Lindrawati Lindrawati; Marini Purwanto; Dian Purnama Sari (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
Learning in basic accounting can generally be grouped as accounting for service companies and accounting for trading companies. Community service activities aim to evaluate the absorption of high school students regarding accounting material, especially in trading companies. This community service activity is carried out by providing online tutorials to ABC High School students in Surabaya, then the students answer the practice questions that have been prepared. The results of this community service activity show that high school students who get the results that the majority of students still have a lot to explore accounting material in trading companies. The results of the evaluation showed that the students had quite good understanding of general journals in trading companies, corrections journals, capital and profit calculations and understanding of the perpetual method. However, students still have difficulty understanding adjusting journals, COGS calculations and understanding the periodic method. Educators can still spur students' cognitive processes by implementing more effective learning so that learning objectives can be achieved.